Assistive Technology to Promote Communication and Social Interaction for People With Deafblindness: A Systematic Review - Dyzel, Vernandi; Oosterom-Calo, Rony; Worm, Mijkje; Sterkenburg, Paula S. (Frontiers in Education, 2020)
Background: People with deafblindness experience stigmatization, exclusion and isolation. Due to complex communication challenges, feelings of isolation and exclusion can increase. However, assistive technology can change these negative outcomes. The aim of this systematic review is to synthesize and analyze the research published in journal articles focused on the use of assistive technology to improve communication and social interaction for people with deafblindness. Methods: A qualitative review study, examining journal articles focusing on the use of assistive technology to support social interaction of people with deafblindness as found in the following databases: IEEE Xplore, ProQuest, Cochrane, Embase, CINANHL, PsychINFO, Web of Science, PubMed and ProQuest, was conducted. An in-depth analysis of the selected articles was performed. Results: Nine articles were included in this systematic review. The Technology Readiness Levels indicated that the communication assistive technologies reported in the included journal articles span across readiness levels, but mostly remained in the prototype phase. The identified themes are: 1) the objective of the assistive technology, with as sub-themes two-way communication and access to information; 2) design and development, with as sub-themes new communication assistive technology design and development, usability and co-creators; 3) acquisition and implementation; and 4) the impact of the assistive technology, with as sub-themes social integration and expansion, autonomy and confidence, and wellbeing. Conclusions: This systematic review provides a roadmap for the way forward in the use of assistive technology in communication and social interaction for people with deafblindness. Co-creation should start during the design and development stages and continue into testing, evaluating and implementation. A greater understanding of the unique communication needs and challenges may contribute to the development of more advanced technologies which can be used in daily situations and contribute to support two-way communication and social inclusion of people with deafblindness. Furthermore, a challenge remains to focus on the development of assistive technology supporting declarative communication, which includes giving comments, declarations, predictions and reflections during a conversation. More research conducted over the long-term is needed to bring the communication assistive technologies into more advanced stages of readiness.